Logo design love : a guide to creating iconic brand identities - Airey, David, 1979- ([Berkeley, California?] : New Riders, 2015)
In Logo Design Love, Irish graphic designer David Airey brings the best parts of his wildly popular blog of the same name to the printed page. Just as in the blog, David fills each page of this simple, modern-looking book with gorgeous logos and real world anecdotes that illustrate best practices for designing brand identity systems that last.
I. The importance of brand identity. We're surrounded -- It's the stories we tell -- Elements of iconic design -- II. The process of design. Laying the groundwork -- Skirting the hazards of a redesign -- Pricing design -- From pencil to PDF -- The art of the conversation -- III. Moving forward. Staying motivated -- Your questions answered -- 31 practical logo design tips -- Beyond the logo.
Includes bibliographical references (page 218) and index.
Keywords: Branding (Marketing); Logos (Symbols) -- Design; Industrial design coordination